Penumbuhan Lapisan Tipis Silikon Amorf Terhidrogenasi dengan Sistem Hot Wire PECVD - Syamsu, Syamsu (Media Eksakta, 2011)
Hydrogenated amorphous silicon (a-Si:H) thin film was grown on the Corning glass-7059 substrate by using hot wire plasma enhanced chemical vapor deposition (HW-PECVD) system. 10% Silane (SiH4) gas diluted in hydrogen (H2) was used as gas sources. Compared with the deposition rate of conventional HW-PECVD system (0.23 Å/s), the deposition rate of HW-PECVD is higher which varies from 0.86 to 0.42 Å/s for filament temperature from 500 oC to 1000 oC at the gas flow rate of 70 sccm. The optical band gap increases from 1.87 eV to 2.18 eV for filament temperature from 500 to 1000 oC at the gas flow rate of 70 sccm. The dark conductivity is highest (1.59x10-11 S/cm) of the film grown at 800 oC filament temperature.